1986
DOI: 10.1007/bf00402774
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the efficacy and toxicity of locoregional chemotherapy of liver tumors with 5-fluoro-2?-deoxyuridine (FUDR) and 5-fluorouracil (5-FU) in an animal model

Abstract: For the investigation of locoregional chemotherapy of liver neoplasms we developed a standardized animal model in the rat. Continuous infusion therapy or repeated bolus injections of FUDR or 5-FU were given via the hepatic artery, the portal vein or the vena cava in tumor-bearing animals. The efficacy of the treatment was determined by measuring the tumor volume 3 weeks after tumor cell implantation. For the evaluation of the local and systemic toxicity serum GOT, GPT, and total bilirubin were determined. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The principle advantages of locoregional arterial infusion therapy over intravenous or intra-portal infusion therapy have been evaluated in solitary tumors growing in the liver (Bartkowski et al 1986). In this study, only the intra-arterial infusion treatment caused significant reduction in tumor growth as well as reduced systemic toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…The principle advantages of locoregional arterial infusion therapy over intravenous or intra-portal infusion therapy have been evaluated in solitary tumors growing in the liver (Bartkowski et al 1986). In this study, only the intra-arterial infusion treatment caused significant reduction in tumor growth as well as reduced systemic toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Current Japanese guidelines recommend HAIC as a treatment option in patients with advanced HCC without extrahepatic metastasis (EHM) [8]. This treatment allows direct delivery of chemotherapeutic agents into tumors feeding hepatic arteries at increased local concentration, and provides strong antitumor effects with lower systemic toxicity via a first-pass effect in the liver [9]. In their study, Nouso et al [10] reported the efficacy of HAIC of 5-fluorouracil (5FU) and cisplatin (CDDP) for advanced HCC with or without macrovascular invasion (MVI) using the Nationwide Survey of Primary Liver Cancer in Japan, which collected initial treatment data from each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Early experiments with rats bearing Novikoff hepatoma cells in their livers have shown that HAI is superior to portal vein infusion (PVI) or systemic administration when using drugs with a high first-path effect in the liver, such as 5-FU ( Bartkowski et al 1986). Subsequent studies with 5-FU in the same model demonstrated that HACE is superior to HAI and that the combination of HACE with PVI is more effective than single or combined regional infusion therapies and even minimally better than HACE alone (Bodeker et al 2003, Kamphorst et al 1999).…”
mentioning
confidence: 99%